2020
DOI: 10.1136/rapm-2020-101812
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative cannabis use: a longitudinal study of associated clinical characteristics and surgical outcomes

Abstract: BackgroundDespite increases in cannabis use generally and for pain management, data regarding cannabis use in patients undergoing surgery are lacking. This study examined the prevalence of cannabis use among patients undergoing elective surgery and explored differences in clinical characteristics and surgical outcomes between cannabis users and non-cannabis users.MethodsThis prospective study included 1335 adults undergoing elective surgery. Participants completed self-report questionnaires preoperative and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 28 publications
0
38
0
Order By: Relevance
“…The results of this study showed higher levels of pain, poorer quality of life, and greater likelihood of using opioids or benzodiazepines in cannabis users compared with non-cannabis users prior to and 3 to 6 months following surgery. 123 Statement 1: Chronic use of THC may worsen postoperative pain, increase postoperative opioid use and precipitate the development of postoperative hyperalgesia. Level of certainty: Moderate Statement 2: There is a lack of high-quality evidence describing the risks of concomitant opioids and cannabinoids in the perioperative period and in addition few studies have addressed the benefits and risks of preoperative cannabinoid tapering.…”
Section: Original Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this study showed higher levels of pain, poorer quality of life, and greater likelihood of using opioids or benzodiazepines in cannabis users compared with non-cannabis users prior to and 3 to 6 months following surgery. 123 Statement 1: Chronic use of THC may worsen postoperative pain, increase postoperative opioid use and precipitate the development of postoperative hyperalgesia. Level of certainty: Moderate Statement 2: There is a lack of high-quality evidence describing the risks of concomitant opioids and cannabinoids in the perioperative period and in addition few studies have addressed the benefits and risks of preoperative cannabinoid tapering.…”
Section: Original Researchmentioning
confidence: 99%
“…[237][238][239] In the acute postoperative phase of care, MI, arrhythmias, stroke, cardiac arrest, and cardiomyopathy have been reported. 123 241 Mittleman et al interviewed 3882 patients with acute MI and conducted a case-crossover analysis that controlled for differences among patients, and found that within 1 hour after smoking marijuana, patients' risk of MI onset was elevated 4.8fold (95% CI 2.9 to 9.5; p<0.001) compared with periods of nonuse. 87 However, in the second hour after smoking, the relative risk was 1.7 (95% CI 0.6 to 5.1; p=0.34), suggesting a rapid decline in the cardiac effects of marijuana.…”
Section: Of Certainty: Lowmentioning
confidence: 99%
See 1 more Smart Citation
“…found that a preoperative history of cannabinoid use resulted in higher pain scores after major orthopedic surgery, as well as greater incidence of sleep interruption; postoperative opioid use was higher among patients who used cannabinoids preoperatively, however this was not statistically significant in this study. A similar article on elective surgery outcomes in patients who used cannabis reflected worse pain, greater functional impairment, and sleep disturbances associated with cannabis use, though overall surgical outcomes were comparable 23 . Thus, cannabinoid use may be a risk factor associated with poorer postoperative pain and consequently higher consumption of opioids after PIV.…”
Section: Discussionmentioning
confidence: 92%
“…A similar article on elective surgery outcomes in patients who used cannabis reflected worse pain, greater functional impairment, and sleep disturbances associated with cannabis use, though overall surgical outcomes were comparable. 23 Thus, cannabinoid use may be a risk factor associated with poorer postoperative pain and consequently higher consumption of opioids after PIV. As cannabinoid use has been reported to be more prevalent in the transgender community in comparison to the general population, this risk factor emphasizes the need to find ways to minimize opioid utilization during the postoperative recovery period for PIV patients.…”
Section: Discussionmentioning
confidence: 99%